2001
DOI: 10.2337/diacare.24.4.631
|View full text |Cite
|
Sign up to set email alerts
|

Basal Insulin Therapy in Type 2 Diabetes

Abstract: OBJECTIVE -To determine the safety and efficacy of the long-acting analog insulin glargine compared with NPH insulin in patients with type 2 diabetes who were previously treated with insulin alone. RESEARCH DESIGN AND METHODS-A total of 518 subjects with type 2 diabetes who were receiving NPH insulin with or without regular insulin for postprandial control were randomized to receive insulin glargine (HOE 901) once daily (n ϭ 259) or NPH insulin once or twice daily (n ϭ 259) for 28 weeks in an open-label, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
246
1
14

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(278 citation statements)
references
References 12 publications
17
246
1
14
Order By: Relevance
“…Curiously, this fact is not mentioned in the original report [44], which concludes with the statement that insulin glargine has a safety profile that, apart from reduced nocturnal hypoglycaemia, is 'otherwise similar to NPH insulin'. Equally curious, a later review also cites the same paper as documenting a three step or greater retinopathy progression in 7.5% of those on insulin glargine vs 2.7% of those on NPH (p<0.05) [45].…”
Section: Insulin Glargine and Retinopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Curiously, this fact is not mentioned in the original report [44], which concludes with the statement that insulin glargine has a safety profile that, apart from reduced nocturnal hypoglycaemia, is 'otherwise similar to NPH insulin'. Equally curious, a later review also cites the same paper as documenting a three step or greater retinopathy progression in 7.5% of those on insulin glargine vs 2.7% of those on NPH (p<0.05) [45].…”
Section: Insulin Glargine and Retinopathymentioning
confidence: 99%
“…A further safety concern requiring human studies arose when one of the early clinical trials [44] was reported to have observed a threefold increase in retinopathy progression with insulin glargine compared with human insulin [41]. Curiously, this fact is not mentioned in the original report [44], which concludes with the statement that insulin glargine has a safety profile that, apart from reduced nocturnal hypoglycaemia, is 'otherwise similar to NPH insulin'.…”
Section: Insulin Glargine and Retinopathymentioning
confidence: 99%
“…98,99 This weight-sparing phenomenon appears to be unique for insulin detemir. While some studies have shown that patients treated with insulin glargine initially gain less weight relative to those treated with NPH, 100,101 no difference between insulin glargine and NPH was noted in patients treated for 1 year. 97 Moreover, in a recently reported study, patients with type 2 diabetes were switched from NPH insulin or insulin glargine to insulin detemir for their basal insulin supply in combination with oral anti-diabetic drugs.…”
Section: Weight Gainmentioning
confidence: 99%
“…Adherence to insulin therapy was reported to be inadequate [30] [31] and numerous factors related to patient and physician perceptions were thought to be responsible for treatment compliance [28]. In our study, a discontinuation rate was of only four percent at the end of 12 months following the initiation of insulin glargine.…”
Section: Discussionmentioning
confidence: 65%